« Mujeres contra la revolución ». La movilización femenina conservadora durante la Segunda República española y la Guerra Civil - Julio Prada Rodríguez (Amnis)
This article explores the origins of the feminine counter-revolutionary mobilization during the Second Spanish Republic and civil war. His first manifestations are related to the fight against the lay policy of the Republican Government and are organized by rural priests. This paper also analyzes the articulation of feminine sections with conservative (CEDA, Traditionalistic) and and fascists (Phalange) parties. It also investigates their action as propagandists and agitators to determine the real reach of this mobilization and its electoral projection on a given geographical area. This paper examines too the role of women during the Spanish civil war from the perspective of the rebels. First of all, it explores the process that leads to the elaboration of the “prototype of Spanish woman” by the Franquist Regime, which essentialy results from the fusion of catholic, traditionalists-carlists and phalangists elements, with clear predominance of the first ones. Finally, it concludes with a brief characterization of the role played by these women in the rearguard during the war.